(untitled) (Open Herald: Periodical of Methodical Research, 2025)
This article focuses on the analysis of the transformation of the engineering training system in Uzbekistan in the era of digitalization. The focus of the study is on the changes in educational policy and approaches to meet the new requirements of the digital economy. The article discusses the issues and prospects of introducing modern technologies in engineering education, as well as training in the context of Industry 4.0. Special attention is paid to modern trends in education and their compliance with international standards. In conclusion, the article presents proposals for improving the system of engineering education in the context of digitalization